Low-temperature processed meso-superstructured to thin-film perovskite solar cells - Ball, J; Lee, M; Hey, A; Snaith, H (2013)
We have reduced the processing temperature of the bulk absorber layer in CH3NH3PbI3-xClx perovskite solar cells from 500 to <150 °C and achieved power conversion efficiencies up to 12.3%. Remarkably, we find that devices with planar thin-film architecture, where the ambipolar perovskite transports both holes and electrons, convert the absorbed photons into collected charge with close to 100% efficiency. © 2013 The Royal Society of Chemistry.